Is Professionalization a must for family managed textile firms in India: A Financial Analysis - Singh, Gian (2009)
This dissertation focuses on the need of professionalizing family managed firms and it also study’s the financial structure of these firms. To empirically show the benefits of recruiting professional managers, financial comparison of family and non-family managed firms has been done in this paper.